The forms of end of the criminal process for misdemeanor. A legislative integration proposal - Abanto Quevedo, Mario Lohonel (2012)
Given the inadequate regulation of criminal proceedings for want of the Code of Criminal Procedure, 2004, this paper intends to integrate the law through the judge’s interpretive activity. This technique is applied to the different ways it can end this kind of criminal trial and are exposed in this essay